Β-Cyclodextrin and Adamantane Polyacrylic Acid Copolymers as Supramolecular Binder for Silicon Anodes: N-Methylpyrrolidone or Water for Preparing the Slurries? - Martin-Trasancos, R; Martin-Trasancos, R (Elsevier Ltd, 2024)
Silicon is a promising material for anodes in future generations of LIBs. However, its volume changes during the lithiation/delithiation process that degrades battery performance, making it an impractical alternative. To mitigate this issue, we have found a viable alternate solution, which is the preparation of adamantane-polyacrylic acid (AdEN-AA) and β-cyclodextrin-polyacrylic acid (βCD6A-AA) polymers as supramolecular binders. The advantage of these binders is that polymers leverage host-guest interactions. To carry out this research, we prepared the anode materials in water and in NMP, and then we studied their capacity to crosslink and gel. Additionally, we examined the extent of the supramolecular interaction vs. hydrogen bond. Thermogravimetric analysis showed that the thermal stability of the mixture of complementary polymer increased in the following order: AdEN-AA/βCD6A-AA in NMP < βCD6A-AA/PAA < AdEN-AA/βCD6A-AA, with the latter two in water. Accordingly, the anode material prepared in water shows the highest stability, retaining capacities of over 1000 mAhg-1 after 90 cycles vs. 279 mAhg-1 of the electrode prepared in NMP. The results agreed with the SEM micrographs of the anode material, in which the slurry prepared in water showed better integrity of the silicon nanoparticles and of solid electrolyte interphase than the slurry prepared in NMP. © 2023